2011
DOI: 10.1002/cphc.201100129
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Effects on Thermodynamics and Phase Equilibria in Oxide Systems

Abstract: Because different solid materials (phases) have different surface energies, equilibria among them will be significantly affected by particle size. This Minireview summarizes experimental (calorimetric) data for the surface energies of oxides and discusses shifts in the stability of polymorphs, the thermodynamics of hydration, and oxidation-reduction reactions in nanoscale oxide systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
188
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(201 citation statements)
references
References 53 publications
11
188
0
2
Order By: Relevance
“…2 nm, would stabilize the cubic phase) [35,36]. Obviously, this particle-size driven structural transition is not a ZrO 2 exclusive situation [37]. It has been frequently concluded that microparticulated samples of these oxides adopt the thermodynamically stable structural variety, whereas those shown by nanoparticulated ones are metastable [38].…”
Section: Resultsmentioning
confidence: 98%
“…2 nm, would stabilize the cubic phase) [35,36]. Obviously, this particle-size driven structural transition is not a ZrO 2 exclusive situation [37]. It has been frequently concluded that microparticulated samples of these oxides adopt the thermodynamically stable structural variety, whereas those shown by nanoparticulated ones are metastable [38].…”
Section: Resultsmentioning
confidence: 98%
“…The low SE of the layered structure CaMnO materials (significantly smaller than for Mn 3 O 4 , Mn 2 O 3 , or MnO 2 ) suggests that water is not strongly bound to the surface sites, because, for many oxides, the enthalpy of H 2 O chemisorption becomes more exothermic with increasing SE (28,(34)(35)(36). In comparing TiO 2 and SnO 2 (rutile structure), Ma et al (35) have argued that the better gas-sensing ability of the latter stems from a lower surface energy, lower water coverage on the surface, and weaker binding of surface water, enabling energetically easier access of other gas molecules to the SnO 2 surface.…”
Section: Discussionmentioning
confidence: 97%
“…Although the relative stability of the polymorphs depends on bulk properties such as the enthalpy of formation and molar volume, the contribution of surface free energy often results in a dependence of stability on crystal size (58,59). This dependence can even invert the sequence of polymorph stability relative to that observed for the bulk phases (58).…”
Section: The Influence Of Surface Energy On Pathwaysmentioning
confidence: 99%
“…Cryo-TEM observations showing coaligned arrays of particles that appear separated by a solvent layer underline the importance of the solvent in mediating attachment (62). Because the solvation energy of a surface generally becomes more exothermic with increasing surface energy (59), the dynamics of CPA should also be affected by surface energies. In particular, high-energy surfaces with loosely held solvent may be more reactive toward other species in the solution, including other particles.…”
Section: The Influence Of Surface Energy On Pathwaysmentioning
confidence: 99%